The effect of organizational support on employee performance: A systematic literature review (Lighthouse Publishing, 2023)
Employees are essential assets for a company's business operations, and the organization's role as an overarching institution is essential to support them. This support is essential for motivating workers and determining the progress or decline of an organization's achievements. Organizational support is also important for determining the progress or decline of an organization's achievements. The purpose of this Systematic Literature Review is to compile studies published between 2018 and 2023 that examine the connection between organizational assistance and worker productivity. The influence of organizational support on employee performance was the subject of this systematic review and meta-analysis, which was prepared using the Preferred Reporting Item. Population, Intervention, Comparison, and Outcome techniques are used to get information from Google Scholar and Digital Reference Garba (Garuda). A total of 79 data points were filtered using data inclusion criteria, yielding a final score of 79. The research found that a favorable and substantial relationship existed between organizational support and performance in 26 out of 50 individual cases. Four items have a detrimental impact on performance significantly because of the assistance they get from their company. This study implies that Organizational support is seen as very important for the behavior of workers/employees. With organizational support, employees feel valued and valued by the organization.